No alteration of leukocyte telomere length in first episode psychosis. (July 2021) - Schürhoff, Franck; Corfdir, Cécile; Pignon, Baptiste; Lajnef, Mohamed; Richard, Jean-Romain; Marcos, Elisabeth; Pelissolo, Antoine; Leboyer, Marion; Adnot, Serge; Jamain, Stephane; Szöke, Andrei
Highlights: There is no accelerated telomere erosion in subjects suffering from first episode psychosis. Excessive shortening of telomeres occurs during the course of schizophrenia. Psycho-social stress /adversities and stressful situations are probably the cause of telomere erosion in schizophrenia. Inflammatory processes and oxidative stress may be involved in the relationship between chronic stress and telomere erosion. Telomere alterations may be considered as a biomarker of illness progression. Abstract: Both shorter telomeres and schizophrenia have been associated with a decrease in life expectancy. Furthermore, several studies found a shorter telomere length (TL) in schizophrenia. Understanding whether or not telomere shortening is directly related to pathophysiology of schizophrenia or is a consequence of a cumulative exposure to chronic stress is of major importance. Comparing the TL of subjects at the very beginning of the disease (FEP) and control subjects could help to decide between these two hypotheses. The aim of the present study was to compare TL between FEP subjects (N=91) and controls (N=137). After accounting for multiple potential confounders, no significant association was observed between FEP and TL. Our result is consistent with the hypothesis that psycho-social stress / adversities and stressful situations in people with schizophrenia affect TL rather than that telomere erosion contributes to the development of this disorder.